Causes and Effects of Flooding in Nigeria: A Review - Ifiok Enobong Mfon; Michael Chukwuemeka Oguike; Salvation Ubi Eteng; Ndifreke Moses Etim (East Asian Journal of Multidisciplinary Research, 2022)
Flooding is an environmental hazard that needs appropriate measures to be instituted to stem the tide of occurrence. The study relied on previous academic/scholarly articles in achieving the aim.  It was noted in the study that flooding is caused by natural and human activities. For instance, excessive rainfall, terrain and nature of soils are natural causes of flooding. Furthermore, poor environmental planning/monitoring, housing development in flood prone areas, deforestation, haphazard developments resulting in the blockage of drains, poor waste disposal practices, negligence by government in designing and implementing policies at various levels as well as poor environmental planning and weak enforcement of policies contribute to flood occurrence. To this end, the present study suggested that government should ensure that environmental management policies are properly enforced in the country. Equally, development control activities should be taken seriously to avoid erecting developments on flood plains and flood prone areas. Finally, regular environmental education should be given priority in the society.